Solvency regulation: An assessment of Basel III for banks and of planned Solvency III for insurers - Peter Zweifel (Journal of Risk and Financial Management, 2021)
Basel III, regulating the solvency of banks, is to be fully implemented by 2027 while Solvency III directed at insurers is being prepared. In view of past experience, it will be closely modelled after Basel III. This raises two questions. (i) Will Basel III and Solvency III be more successful than their predecessors? (ii) Is it appropriate to continue regulating the solvency of banks and insurers in the same way? The first question is motivated by an earlier finding that Basel I and II risked inducing more rather than less risk-taking by banks, which also holds for Solvency I and II w.r.t. insurers. The methodology applied was to determine the slope of an endogenous perceived efficiency frontier (EPEF) in (μ,σ)-space derived from banks' and insurers' optimal adjustment to exogenous changes, in expected returns dμ and volatility dσ on the capital market. Both Basel I and II and Solvency I and II neglected the impact of these developments on banks' and insurers' EPEF. This neglect had the effect of steepening the EPEF, causing senior management to opt for an increased rather than reduced value of σ, and hence a lower solvency level. This issue is resolved by Basel III (Principle 5), which requires banks to take developments in the capital market into account in the formulation of their business strategies designed to ensure solvency. In combination with increased capital requirements, this is shown to result in a reduced slope of their EPEF and hence a reduced risk exposure. However, planned Solvency III may cause the EPEF of highly capitalized insurance companies to become steeper, with a concomitant decrease in their risk-taking and an increase of their solvency level. The second question, concerning the appropriateness of the uniformity of solvency regulation directed at banks and insurers, arises because the parameters determining the slope of the respective EPEF are found to crucially differ. Therefore, the uniformity of Basel and Solvency norms creates the risk of a mistaken regulatory focus.
Keywords: G15; G21; G28; L51; 330; Basel III; banks; Basel I; Basel II; insurers; regulation; Solvency I; Solvency II; Solvency III